ICHTHYOFAUNA IN THE INNER CONTINENTAL SHELF NEXT TO THE PARANAGUÁ ESTUARINE COMPLEX, SOUTHERN BRAZIL - Cesar SANTOS; Roberto SCHWARZ JUNIOR; Helen Audrey PICHLER; Olímpio Rafael CARDOSO; Marcelo Renato LAMOUR; Henry Louis SPACH (Boletim do Instituto de Pesca)
The composition and structure of fish assemblages in the inner continental shelf of the Paraná State are affected by cold fronts and the rainfall regime. Data from fishing activities in this region, as well as the analysis of environmental characteristics, are the main tools available for understanding fish dynamics, under influence of increasing human activities. In order to better understand patterns and temporal variations in fish assemblages in the inner continental shelf of the Paraná State, a total of 24 double trawls were performed with an otter trawl between August 2000 and July 2001, in two sampling areas, the North area in front of the northern mouth of the Paranaguá Estuary Complex, and the South area, in front of the Leste beach. A total of 45,277 fish specimens belonging to 35 families and 97 species were caught. Sciaenidae was the most abundant family, with 37.1% of the total number of individuals caught, and with the highest richness (18 species). Statistical analyses evidenced significant differences in environmental characteristics and in fish fauna, and that both areas disturbances were observed in the fish assemblages during the dry and wet season, being more intense in the Southern area, disturbances that would be related to the shrimp fishing present in the two areas sampled in this study.